TRADISI DAN SASTRA LISAN SEBAGAI PEWARISAN NILAI-NILAI LUHUR MASYARAKAT BADUY (Oral Traditions and Literature as the Inheritance of Baduy’s Great Values) - Dody Kristianto, Nur Seha (Balai Bahasa Sumatra Barat, 2016)
This study aims to reveal the type of oral literature living in the Baduy community, as well as the functions and values contained therein. This study used James Danandjaya’s folklore theory. Data collection was conducted by using a combination of field tecnics (interviews and record) and libraries.The data analysis is performed at the word level and the fabric of words. Furthermore, the interpretation on getting the message, meaning and function was preceded with transcription and trasliteration data. This study has invented some oral literatures living in Baduy, some of them are pitutur(Baduy people’s history or narrative story); pikukuh (custom rules that must be adhered by people inside Baduy and outside Baduy); and tanda basa (utterances spoken for approximately ten to fifteen minutes by an interpreter (called juru basa) in a certain traditional ceremonies). Based on the results of the data analysis, it revealed, hat the function of oral literature in Baduy are as a means of cultural ratification, as the enforcement of coercive social norms, as a social control, and as an education for their children. Meanwhile, the value contained inside them are the value of honesty, decency, and compliance.